Addressing Comorbid Anxiety in Family Based Treatment for Adolescent Anorexia Nervosa User Experiences and Perspectives - Mette Bentz; Rikke Barslund Gregersen; Viktoria Vinther Ottsen; Irene Lundkvist-Houndoumadi; Signe Holm Pedersen (Global Journal of Medical Research, 2023)
Purpose This study examines three families experiences of the influence of comorbid anxiety on the effectiveness of family-based treatment FBT for anorexia nervosa AN and the effect of an add-in module addressing comorbid anxiety and how this might interact with the families work on AN and the young person s YP s sense of self-efficacy Method Qualitative interviews were carried out with three families who had been offered an add-in module at The Child and Adolescent Mental Health Centre of the Capital Region of Denmark All interviews were analysed using thematic analysis